Implementation of ERACS to Optimize High-Demand Delivery Services at a Secondary Public Hospital in The Jakarta Region - Oktavia, Eva; Wahyoedi, Soegeng; Gunardi, Wani Devita (Universitas Padjadjaran, 2023)
The Enhanced Recovery After Cesarean Section (ERACS) method is an effort to improve the quality of cesarean delivery service through standardization of perioperative management, supported by evidence-based medicine. This study assessed the impact of implementing ERACS method on hospital service quality, focusing on patient recovery time and satisfaction. Furthermore, it also measures the influence of age and educational background in moderating the effect of service quality. A prospective cross-sectional study was conducted using a consecutive sampling method on 75 patients who underwent ERACS and were selected according to the inclusion criteria. Documentation on patients’ perception of service quality and satisfaction was reviewed post-surgically before discharge. The hypothesis test showed that ERACS has a significant positive effect on patient satisfaction (β= 0.9, p= <0.05), and it has a significant negative effect on length of hospital stay (β= -0.29, p= <0.01). Age and educational background did not moderate the effect of ERACS on patient satisfaction (β= 0.001, p= >0.05 and β= 0.01, p= >0.05, respectively). The education factor also did not moderate the effect of ERACS on the length of hospital stay (β= 0.01, p= >0.05). In contrast, the age factor moderated the effect of ERACS on the length of hospital stay (β= 0.31, p= <0.05). The ERACS method is feasible to be carried out at a level two public hospital with good patient outcomes and satisfaction. Young aged group of patients were good candidates for ERACS accelerated recovery time protocol.